Pengelolaan arsip vital pada Kantor Dinas Kependudukan dan Pencatatan Sipil Kota Sibolga - El Shifa Alhafisa Nasution; Darmayanti Darmayanti (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2020)
This research was conducted at the Office of the Civil Population and Recording Office of Sibolga City, the purpose of this research is to find out about the management of vital archives. The study used a type of internal evaluation. The type of research used is qualitative research with a descriptive approach. The data collection techniques used in this study are interviews, observations, and documentation studies. The results showed that the management of vital archives conducted at the Office of the Civil Population and Recording Office of Sibolga City has not been in accordance with PERKA ANRI No. 49 of 2015 on the Guidelines of the Vital Archives Program in the Environment of the National Archives of the Republic of Indonesia. Identification is done by looking at the nature and subject matter of the document. Documents that include vital archives are resident files, staffing files, financial files, and correspondence of an important nature. Vital archive setup is done in 4 ways, namely inspection, index determination, labeling, and placement of archives. Sibolga City Civil Registry and Population Office does not have a list of vital records. No method of protection and physical security of vital archives is carried out. For electronic files vital archives in the form of resident files are carried out protection and security by using SIAK application. No method of physical rescue and recovery of vital archives is damaged or destroyed, but the electorate files of populated files stored in the SIAK application can be reprinted.